Triple-valve endocarditis due to Lysinibacillus sphaericus infection - Jordan L. Torres; Jason R. Faulhaber (IDCases, 2023)
Lysinibacillus sphaericus is an environmental organism often considered a contaminant when isolated from patient specimens due to its rare association with human disease. Here we report a case of triple valve endocarditis caused by L. sphaericus infection. To the authors’ knowledge, this is the first documented case of endocarditis caused by this bacterium.